Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Problem Based Learning Berbasis Media Pop Up pada Materi Bangun Ruang Kelas IV SD Al Azam Semarang - Pratama, Gilang; Prayito, Muhammad (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
This research was motivated by the low learning outcomes of students. The aim of the research is to improve the mathematics learning outcomes of AL AZAM Elementary School students by using the Problem Based Learning learning model. This research uses quantitative and qualitative research with descriptive methods. The research carried out focused on class IV students at SD AL AZAM Semarang, totaling 25 students with different levels of ability. Based on the results of the research and discussion, it can be concluded that by using the Problem Based Learning learning model and assisted by Pop-Up Book learning media in mathematics subjects, student learning outcomes can increase. The increase in learning outcomes from cycle I was initially only 24% and increased in cycle II to 80%. Observations on students' activities during the learning process using the Problem Based Learning learning model are in the good category so that the Problem Based Learning method is very effective in learning mathematics regarding building materials.